2023
DOI: 10.1002/pd.6418
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of cleft lip and/or palate: What do we tell prospective parents?

Abstract: Cleft lip and/or palate (CL/CP) is the most common congenital craniofacial anomaly and parents often ask, “how did this happen?” Patients and families may benefit from access to a multidisciplinary team (MDT) from prenatal diagnosis into early adulthood. Multiple factors can contribute to the development of a cleft. We discuss the epidemiology and risk factors that increase the likelihood of having a newborn with a cleft. The purpose of this article is to review the prenatal investigations involved in the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The prenatal detection of cleft palate remains a challenge [39]. However, the arrival of artificial intelligence is a positive aspect in addressing these patients, as it has been demonstrated that deep learning models revolutionize the diagnostic process, predict susceptibility to CLP, and enhance alveolar bone grafts and orthodontic treatment [40,41], assisting caregivers in reducing the burden associated with the process of this pathology [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The prenatal detection of cleft palate remains a challenge [39]. However, the arrival of artificial intelligence is a positive aspect in addressing these patients, as it has been demonstrated that deep learning models revolutionize the diagnostic process, predict susceptibility to CLP, and enhance alveolar bone grafts and orthodontic treatment [40,41], assisting caregivers in reducing the burden associated with the process of this pathology [42,43].…”
Section: Discussionmentioning
confidence: 99%